About the educational environment of a cloud platform for managing and modeling a variable structure in sliding mode - V. S. Mkrtchian; N. I. Shyjan (Academy of Cognitive and Natural Sciences, 2013)
Poltava National Pedagogical University and Astrakhan State University as a part of the consortium, prepared a joint application for the competition of joint Russian-Ukrainian initiative projects on the theme: "Variable structures and control in sliding modes on the platform of cloud applications for virtual modeling and design of new composite materials of multifunctional purpose". The project proposes for the first time the design of new composite materials for multifunctional purposes to be elevated to a cloud application platform where variable structures are modeled and controlled in sliding mode. The created cross-platform cloud application platform based on human-avatar oriented interface of new generation virtual modeling with cyber-physical design of control and modeling systems will be enough for practical use in scientifically grounded design of composite materials of multifunctional purpose.